2014
DOI: 10.1007/s00284-014-0742-1
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Tetracycline Resistance Genes with Aggregation Substance in Food-Borne Enterococcus faecalis

Abstract: Enterococcus faecalis has the ability to conjugate with the aid of aggregation substance (AS) and inducible sex pheromones to exchange genetic elements in food matrix. To evaluate the food safety condition and the transferable factor, 250 tetracycline-resistant food-borne E. faecalis were collected in Korea. Among the isolates, a majority of tetracycline-resistant isolates (49.6 %) harbored both the tet(M) and tet(L) genes together, followed by tet(M) (19.6 %), and tet(L) (6.8 %) alone. Also, we found the comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 44 publications
4
30
0
6
Order By: Relevance
“…The profiles of virulence genes were less diversified (only three profiles) and strictly correlated with phenotypic resistance profiles. The linkage between resistance and presence of selected virulence determinants has been confirmed previously [ 53 ]. The genome of all the strains tested in our study included genes encoding sex pheromones ( cpd , cob , ccf ) and most of the strains (from profiles A and C) exhibited the presence of the agg gene.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The profiles of virulence genes were less diversified (only three profiles) and strictly correlated with phenotypic resistance profiles. The linkage between resistance and presence of selected virulence determinants has been confirmed previously [ 53 ]. The genome of all the strains tested in our study included genes encoding sex pheromones ( cpd , cob , ccf ) and most of the strains (from profiles A and C) exhibited the presence of the agg gene.…”
Section: Discussionsupporting
confidence: 68%
“…The agg gene was detected using the highly conserved sequence characteristic for representatives of the class of pheromone-responsive plasmids ( pAD1 , pPD1 , and pCF10 ) [ 54 , 55 ]. The family of these plasmids shows high frequency of conjugative transfer of antibiotic resistance and virulence genes from donor cells by mating sex pheromones produced by potential recipient cells [ 53 , 54 ]. The aggregation substance promotes cell conjugation by bacterial aggregation, which results in close contact between the donor and recipient cells [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Death cases from Aeromonas infection [27] and Acinetobacter [28] were also reported in South Korea. Interestingly, Kim et al [10], Jun et al [27] and Choi and Woo [29] reported that the tet(M) gene was the most prevalent antibiotic resistance gene found in food, with the possibility of resistance gene transfer to other food-borne bacteria. For these reasons, whether antibiotic-resistant bacteria found in Wando and Geoje sites represent a risk for human health in South Korea must be examined further.…”
Section: Identification Of Oxytetracycline-resistant Bacteria Suggestmentioning
confidence: 99%
“…Hence, food-borne E. faecalis may affect the quality and security of food, which has potentially serious implications for pregnant women. Many recent studies have focused on safety assessment of E. faecalis isolates from foods [7,8]. However, knowledge of the molecular mechanisms that E. faecalis employs to traverse the host placental barrier remains unclear.…”
Section: Introductionmentioning
confidence: 99%